RESULTS OF ABNORMAL ANTIBODY SCREENING AT VINMEC TIMES CITY INTERNATIONAL GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the results of irregular antibody screening tests performed at Vinmec Times City International General Hospital from 2023 to 2025.Subjects and methods: The study was conducted from July 2023 to June 2025 at the Laboratory Department of Vinmec Times City International General Hospital. A total of 1503 specimens from 923 patients were tested for irregular antibodies using gel cards on the Ortho Vision automated analyzer. Study design: cross-sectional descriptive study.Results: Among 1503 tested specimens, the overall positive rate was 3.73%, with a higher proportion in females than in males. Patients with a history of blood transfusion showed a higher positive rate. Seven disease groups were indicated for testing; among them, gastrointestinal and hematologic diseases had the highest positive rates, while surgical and cardiovascular groups showed lower rates. The positive rate tended to increase in repeat tests during treatment, with six cases converting to positive after blood transfusion.Conclusion: Overall positive rate was 3.73%, higher in females than in males. Patients with a history of blood transfusion and those with hematologic or gastrointestinal diseases have higher positive rate. Repeat testing during treatment is necessary to detect newly formed irregular antibodies and ensure transfusion safety.
Keywords: Abnormal antibodies, screening tests, blood transfusions.